Chaetosphaeria tortuosa, the newly discovered teleomorph of Menispora tortuosa, with a key to known Menispora species - Réblová, Martina; Seifert, Keith A; White, George P (Mycological research, 2006)
Chaetosphaeria tortuosa is described as the newly discovered teleomorph of Menispora tortuosa, based on specimens from Canada and the Czech Republic, and single spore isolations from both morphs. The fungus produces superficial, more or less globose, papillate, dark brown to black smooth perithecia (200-)220-250 x (220-)230-260 microm. The asci are unitunicate, 8-spored, cylindrical-fusiform, (110-)120-133(-145) x 12-14 with a distinct apical, nonamyloid annulus 1-1.5 microm high, 3.5-4 microm wide. The ascospores are fusiform, 19-24 x 5-6 microm, hyaline, 3-septate, smooth, and 2-seriate in the ascus. The morphology of the teleomorph and anamorph are similar to that of C. ovoidea (anamorph: M. glauca), differing in dimensions of asci and ascospores, and in the disposition and morphology of the phialides of the anamorphs. The generic concept and phylogeny of Menispora is briefly discussed, and a key to the 11 species currently accepted in the genus is provided.
Keywords: Ascomycota